Pengaruh Motivasi Kerja Dan Komitmen Organisasional Terhadap Kinerja Karyawan - Muhammad Muinul Hamid; Abdul Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstracEvery organization or business unit must be able to optimize human resources and manage human resources. Personnel management is closely related to the factors of employees who are expected to do their best to achieve the goals of the organization or business unit. Employees are the most important organizational assets and play a strategic role in the organization as thinkers, planners and controllers of organizational activities. To achieve organizational goals, employees must be motivated to work diligently and sincerely.Given the importance of labor in the organization, more attention must be paid to the work of employees to achieve organizational goals. With high motivation, employees will do their work harder. Conversely, employees with low work motivation have no morals, are easily resolved and difficulties are resolved. Employees do not have a positive effect on beneficiaries, that is, they allow organizations to debate information about individuals or groups.Keyword: motivation, organizational commitment, performance